Firm dynamics in East Germany: first empirical results - Dietmar Harhoff; Konrad O. Stahl (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
In this paper, we report results of an ongoing empirical analysis of firm dynamics in East Germany. After discussing specifics of a newly available data set with information on more than 100.000 firms, we analyze patterns of business starts and failures. Furthermore, we present preliminary results on employment, revenue and labor productivity growth in East German firms. They suggest that large East German enterprises are characterized by significant labor shedding and small or no nominal revenue growth, resulting in an apparently impressive gain in labor productivity. Small firms turn out to be the carriers of employment growth. On average, they experience the highest revenue growth rates. However, the combination of revenue and employment growth yields labor productivity increases well below those of larger firms.
Keywords: 330; Unternehmensentwicklung; Unternehmensgründung; Konkurs; Betriebsgröße; Neue Bundesländer